Improving Sales Management and Performance – the case of Thyssenkrupp Materials Vietnam’s Hanoi office - Le, Thi Thuy (Khoa Quốc tế, ĐHQGHN, 2020)
The dissertation is to evaluate the competency of Thyssenkrupp Materials Vietnam and discuss the implications to how Thyssenkrupp Materials Vietnam could improve the performance. The research helps to understand the current situation, advantages and difficulties of Thyssenkrupp Materials Vietnam at the moments. The research found challenges in sales management from the sales force and from the environment. The research propose 2 groups of solutions – the first is to improve the sales management control, and the second is to improve the sales.